2010
DOI: 10.1111/j.1532-950x.2010.00660.x
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Quality of Canine Cranial Cruciate Ligament Disease Information Available on the Internet

Abstract: CCL disease information on the Internet is of variable quality and can be misleading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 12 publications
1
28
0
Order By: Relevance
“…However, the Internet is an extensive resource and thus there is the risk for pet owners to access inaccurate and unreliable information, potentially influencing pet health and veterinarian–client relationships (4, 5). This has been previously demonstrated, as Taggart et al (6) evaluated 44 website related to canine cruciate ligament disease and found that the quality of website contents varied and was influenced by both terminology used and if the website was authored by a veterinarian. In addition, Hofmeister et al (3) reviewed websites relating to anesthesia in dogs and found that these were generally found to be incomplete and even potentially misleading in relation to stated risks relating to specific breeds.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…However, the Internet is an extensive resource and thus there is the risk for pet owners to access inaccurate and unreliable information, potentially influencing pet health and veterinarian–client relationships (4, 5). This has been previously demonstrated, as Taggart et al (6) evaluated 44 website related to canine cruciate ligament disease and found that the quality of website contents varied and was influenced by both terminology used and if the website was authored by a veterinarian. In addition, Hofmeister et al (3) reviewed websites relating to anesthesia in dogs and found that these were generally found to be incomplete and even potentially misleading in relation to stated risks relating to specific breeds.…”
Section: Introductionmentioning
confidence: 76%
“…Veterinarians highlighted the concern for pet owners as only 7% of veterinarians thought that between 60 and 100% of clients understand what they read online. Previous studies have found that online pet health information can lack accuracy and completeness (3, 6, 7). This may be further complicated through client search strategies, as veterinarians may use and/or suggest specific reliable pet health websites in mind whereas clients may simply search through search engines and pick sites with minimal additional information.…”
Section: Discussionmentioning
confidence: 99%
“…A common recommendation from these studies has been an increase in accurate online veterinary health information presented at lower reading levels, since much of the information presented at a reading level that impedes many owners from being able to understand the material 8,21,22 .…”
Section: Validity and Reliability Of Health Websitesmentioning
confidence: 99%
“…Kogan et al found similar findings for US pet owners and highlighted the importance of accurate, complete and transparent online pet health information. Previous studies that reviewed canine health websites, focusing on specific canine‐related health websites, have emphasised similar concerns . Website security and privacy settings are important aspects to consider for both pet owners and veterinary staff .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies that reviewed canine health websites, focusing on specific canine-related health websites, have emphasised similar concerns. [12][13][14] Website security and privacy settings are important aspects to consider for both pet owners and veterinary staff. 15 Yet, even when websites are secure, current, unbiased and accurate, there is still a risk for misinterpretations by the user.…”
Section: Introductionmentioning
confidence: 99%